The Real Effects of Monetary Policy in the European Union : What Are the Differences? - Ramaswamy, Ramana (IMF Working Papers; Working Paper ;, 1997)
The main finding of this paper is that the European Union (EU) countries fall into two broad groups according to the effects of monetary policy adjustments on economic activity. Estimates based on a vector autoregression model indicate that the full effects of a contractionary monetary shock on output in one group of EU countries (Austria, Belgium, Finland, Germany, Netherlands, and United Kingdom) take roughly twice as long to occur, but are almost twice as deep as in the other group (Denmark, France, Italy, Portugal, Spain, and Sweden). The paper discusses the implications of these results for the effective conduct of monetary policy in the euro area.